Numerical Analysis on The Effect of Barge Motion to Jacket Lifting Process During Decommissioning - Murdjito Murdjito; Vebby A. Kurniawan; Raditya D. Riyanto; Rudy W. Prastianto (International Journal of Marine Engineering Innovation and Research, 2023)
Offshore structure decommissioning is mandatory when an offshore oil and gas platform reaches the end of its service life. There are no less than 450 fixed offshore steel structures in Southeast Asia, and by 2030, more than 200 offshore fields will be terminated and need to be decommissioned. From an operational aspect, the decommissioning process is simply an inverse of installation. However, due to the structures' age and the uncertainties of the structural performance, the simple operation can be an obfuscating process. This paper discusses one of the most crucial processes during decommissioning: lifting. The dynamic performance of a lifted jacket in several rigging variations is investigated. We use a standard stern crane HLV (Heavy Lift Vessel) to simulate the process, with several wave attack angles. Sea condition is according to DNVGL benign wave during marine operation, with random waves generated using the JONSWAP spectrum. Coupled dynamics of HLV and jacket motion are analyzed.